2013
DOI: 10.1007/s00702-013-1111-0
|View full text |Cite
|
Sign up to set email alerts
|

Gait control and executive dysfunction in early schizophrenia

Abstract: Dysexecutive functioning, which is described as an enduring core feature of schizophrenia, has been associated with gait disorders. However, few studies have reported gait disorders in schizophrenia patients. The objective of this study was to examine the association between executive dysfunction and gait performance in recent-onset schizophrenia patients using the dual task paradigm. Thirty-two subjects participated to the study: 17 with recent-onset schizophrenia and 15 healthy age-matched controls. Executiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Like Putzhammer and colleagues [ 41 ], we identified a significantly decreased gait velocity in patients compared to controls, which can be ascribed to a shorter stride length, not to a decreased cadence. Similarly to Lallart and colleagues [ 40 ], who compared the stride-to-stride variability of patients and controls in a “walk alone” and in dual-task conditions and found significant differences in the dual-task conditions only, we did not find group differences concerning the variation of cadence in simple walking. An increased intraindividual variability in kinematic indices such as peak velocity and peak acceleration was also found by Jahn et al, who developed a device to analyse repetitive pronation/supination for subtle kinematic changes [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 87%
“…Like Putzhammer and colleagues [ 41 ], we identified a significantly decreased gait velocity in patients compared to controls, which can be ascribed to a shorter stride length, not to a decreased cadence. Similarly to Lallart and colleagues [ 40 ], who compared the stride-to-stride variability of patients and controls in a “walk alone” and in dual-task conditions and found significant differences in the dual-task conditions only, we did not find group differences concerning the variation of cadence in simple walking. An increased intraindividual variability in kinematic indices such as peak velocity and peak acceleration was also found by Jahn et al, who developed a device to analyse repetitive pronation/supination for subtle kinematic changes [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 87%
“…Potentially, advances in sensor technology can contribute to providing such real‐time objective measures of functional biomarkers . For instance, a common symptom of schizophrenia is disorganized or abnormal motor behavior which could be detected or even continuously monitored by wearable sensor systems . Additionally, sensors that analyze a patient's voice may be able to detect the monotone speech patterns that are sometimes associated with schizophrenia .…”
Section: Managing Mental Health Disorders: the Schizophrenia Examplementioning
confidence: 99%
“…Previous studies have also found that gait variability is associated with cognitive performance in elders 12 and people suffering from central neurologic damage. [13][14][15] As for people with multiple sclerosis, we recently reported on a sample of 355 individuals with multiple sclerosis without a history of falls, whose increased step time variability was significantly associated with poor global cognitive scores, specifically executive function and motor skills. 16 In a recent study sample of 191 people with multiple sclerosis, cognitive processing speed was found to be a significant predictor of step time/length variability.…”
mentioning
confidence: 99%